Pukaḻēntippulavar ceyta Naḷaveṇpā - Irājakōpālap Piḷḷai, Kō (SAMP early 20th-century Indian books project ;, 1923)
Commentary on Naḷaveṇpā, narrative poem on Nala and Damayanti (Hindu mythology), by Pukalentip Pulavar, 12th century Tamil poet.